SUSPENSION BASED ON A MIXTURE OF TITANIA-SILICA-FUNCTIONALIZED GRAPHENE OXIDE FOR SURFACE CONSOLIDATION OF HISTORICAL ANDESITE STONE AND MORTAR - COTEȚ, Liviu Cosmin; SĂLĂGEAN, C.; MIHIȘ, Alin Grig; SZÉKELY, István-Attila; TÓTH, Zsejke Réka; BAIA, Lucian; BAIA, Monica; OLTEANU, Gabriela; OLTEANU, Iulian Daniel; DANCIU, Virginia (Studia Universitatis Babeș-Bolyai Physica, 2022)
Three-components suspension, based on a mixture of titania (TiO2)-silica (SiO2)-functionalized graphene oxide (GO) is prepared and used for surface consolidation of historical andesite stone and mortar. For comparison, mono- and bi-component suspensions are also involved in this study. In order to increase the attachment capacity of GO to substrate with silicon, GO functionalized with (3-aminopropyl) triethoxysilane (GO-APTES) was involved. Unmodified and modified by painting with prepared suspensions andesite and mortar samples were investigated by microscopy (Optic and SEM-EDX), XRD, FT-IR and Raman spectra before and after 6 months of exposure to ambient conditions. After investigation, even the amount of used consolidant suspension was low, the stability of the modified samples was found that remains constant and in a long time it is possibly to reach even a higher stability level. This approach provides the idea that the prepared suspension could be an interesting option to be involved in stone and mortar consolidation-restoration field.